EVALUASI RISIKO KREDIT DAN LIKUIDITAS TERHADAP KINERJA PROFITABILITAS BANK BUMN DI BURSA EFEK INDONESIA - Andi Zulfakar, Yudha; Nurlaela (ISAFIR: Islamic Accounting and Finance Review, 2025)
This study aims to determine the effect of credit risk (NPL) and liquidity risk (LDR), both partially and simultaneously, on profitability performance as measured by Return on Assets (ROA) at state-owned banks listed on the Indonesia Stock Exchange during the period 2020–2023. This study uses a quantitative approach with secondary data obtained from the annual financial reports of four state-owned banks in Indonesia. The analysis technique used is multiple linear regression. The results of the study indicate that credit risk (NPL) has a negative and significant effect on profitability (ROA), indicating that increasing non-performing loans has an impact on decreasing ROA. In addition, liquidity risk (LDR) has a negative and significant effect on profitability (ROA), indicating that credit distribution that exceeds funding capacity can reduce profitability. Simultaneously, these two types of risks have also been shown to have a significant effect on profitability. These findings emphasize the importance of optimal risk governance capabilities, especially credit and liquidity risks, in maintaining the financial performance of state-owned banks in Indonesia.